FACTORS ASSOCIATED WITH DIETARY SUPPLEMENTS PURCHASE AMONG ADULTS IN MALAYSIA: FINDINGS FROM A NATIONWIDE SURVEY - Chan Yee Mang; Ab Rahim, Iqbal; Khaw Wan-Fei; Jawahir, Suhana (Malaysian Journal of Public Health Medicine, 2024)
Dietary supplements have grown in popularity in the healthcare industry over the years, owing to increased health awareness and health literacy. Understanding the factors associated dietary supplement purchase is critical for policy development and effective regulatory implementation. This paper aimed to describe the prevalence and factors associated with dietary supplements purchased among the adult population in Malaysia. Cross-sectional data from 11,269 respondents aged 18 and above from the Malaysian National Health and Morbidity Survey 2019 were analysed. This study used logistic regression analysis to identify the factors associated with dietary supplements purchased among the adult population in Malaysia. Overall, 13.9% Malaysian adults reported purchasing dietary supplements in the past one month. Females, adults older than 36 years old, individuals with at least a secondary educational level, Chinese ethnicity, the married population, those with higher household income (in the T20 household income group), individuals with diabetes or hypertension or hypercholesterolaemia, and those with perceived good self-rated health were all associated with a higher likelihood of purchasing dietary supplements. The study's findings improved understanding of the factors associated with dietary supplement purchase, which will aid policy development and effective regulatory implementation.